Essential commodities prices, availability, and market actors’ perceptions: April 2025 - Siddig, Khalid; Nigus, Halefom Yigzaw; Mohamed, Shima; Abushama, Hala; Rakhy, Tarig (International Food Policy Research Institute, 2025)
This report presents an overview of trends in prices, availability, and quality of key commodities in Sudan during February, March, and April 2025. It covers cereals, vegetables, animal products, and essential goods such as cooking oil, sugar, agricultural inputs (fertilizers and seeds), fuels, and exchange rates. The analysis reveals notable spatial and temporal disparities in prices, availability, and quality across Sudan’s 18 states. Cereal prices showed mixed patterns: wheat prices rose from February to March before declining in April, while sorghum and millet prices fluctuated. Wheat flour prices remained relatively stable. Spatial disparities were particularly evident for wheat and wheat flour. Traders consistently reported stable availability and quality for most cereals. Vegetable prices varied significantly. Tomato prices remained stable, potato prices were consistently higher than other vegetables, and onion prices declined steadily before rising slightly at the end of April. Spatial and temporal differences in prices were also prominent. Meat prices continued to increase steadily, while fish prices fluctuated in line with availability. Egg prices rose gradually, while milk prices, after some initial fluctuations, declined steadily in March and April. Among agricultural inputs, wheat seed prices remained stable, whereas local sorghum seed prices rose consistently. Fertilizer prices fluctuated: urea prices experienced a modest increase fol lowed by a decline, while DAP prices rose sharply in April. Fuel prices demonstrated both temporal and spatial variability. Prices were notably higher in the parallel market, while diesel and petrol prices in the regular market were more stable, though regional differences persisted. Finally, the exchange rate analysis showed a continued premium in the parallel market, underscoring persistent foreign currency supply constraints.